Teaching styles in physical education: the effects on physical activity levels of middle school students with different motivation types - Hwang, Yongju (My University, 2018)
Self-determination theory (SDT) has been widely investigated to understand and change an individual’s physical activity (PA) behavior in different settings (Deci & Ryan, 1985; 1991; 2000). The first purpose of this study was to examine if physical educators’ teaching style influences student needs that affect student motivation, which in turn predict objectively measured student PA and MVPA levels (i.e., a serial mediator model). The second purpose was to explore moderating role of students’ gender on those relationships. 313 students from three middle schools in Wisconsin completed Learning Climate Questionnaire modified from Williams and Deci (1996), Psychological Need Scale and Need Frustration Scale adopted from Chen et al. (2015), and Physical Education Questionnaire modified from (Aelterman et al., 2012) in a row to assess perceptions of autonomy-supportive teaching, experience of need satisfaction and need frustration, and motivational outcomes, respectively. Participants’ PA and MVPA levels were recorded using a GT3X+ accelerometer (Actigraph, Pensacola, FL) for four consecutive PE lessons. It was found that although there was no gender effect on the relationships of SDT constructs, there was an indirect mediating effects of competence satisfaction and intrinsic motivation between autonomous teaching style and the students’ objectively measured PA and MVPA levels. The results showed that PE teachers’ autonomous teaching behavior is effective to promote students’ objectively measured PA behavior during physical education lessons. Therefore, it is worth paying attention to how to provide autonomous teaching to students efficiently in the PE setting.
Keywords: Physical education and training; Motivation in education